2019
DOI: 10.3390/biom9090398
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic Compounds and Metal Complexes in Current and Future Treatments of Inflammatory Bowel Disease and Colorectal Cancer—a Critical Review

Abstract: In recent years, there has been a significant increase in the clinical use of organometallic compounds and metal complexes for therapeutic purposes including treatment of inflammatory bowel diseases (IBD). Their action is based on the inhibition of the inflow of pro-inflammatory cytokines, the elimination of free radicals or the modulation of intestinal microbiota. In addition, these compounds are intended for use in the diagnosis and treatment of colorectal cancer (CRC) which is often a consequence of IBD. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 101 publications
(134 reference statements)
0
10
0
Order By: Relevance
“…Since the discovery of platinum anticancer properties and the use of cisplatin, a platinum-based alkylating agent, and its derivatives in chemotherapy (37)(38)(39), other metal-based drugs have been designed and developed for their cytotoxic effects on tumour cells (40)(41)(42). Transition metals from the d-block of the periodic table (groups 3 to 12) (43)(44)(45)(46) are particularly suitable for this purpose as they adopt a wide variety of coordination geometries (47). Among them, copper modifies the backbone of the complexed ligand and grants better DNA affinity (48)(49)(50).…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of platinum anticancer properties and the use of cisplatin, a platinum-based alkylating agent, and its derivatives in chemotherapy (37)(38)(39), other metal-based drugs have been designed and developed for their cytotoxic effects on tumour cells (40)(41)(42). Transition metals from the d-block of the periodic table (groups 3 to 12) (43)(44)(45)(46) are particularly suitable for this purpose as they adopt a wide variety of coordination geometries (47). Among them, copper modifies the backbone of the complexed ligand and grants better DNA affinity (48)(49)(50).…”
Section: Introductionmentioning
confidence: 99%
“…Silver nanoparticles (AgNPs) are one of the metal nanoparticle types viewed as potential topical anti-inflammatory agent for treatment of inflammatory bowel diseases (IBDs) such as Crohn's disease, ulcerative colitis, and colonic cancer [1][2][3]. The intestinal inflammation disorder mediated by the immune system is a typical feature of IBD.…”
Section: Introduction mentioning
confidence: 99%
“…Inflammation is a natural body's response to tissue damage. However, it can cause improper tissue repair and contribute to the development of cancer through genotoxic mechanism in the longterm [1]. In-vitro studies reported that AgNPs show drugs can take place in colon.…”
Section: Introduction mentioning
confidence: 99%
“…[2][3][4][5][6][7][8] Transition metal complexes have emerged as a viable alternative to organic compounds with distinct biological properties and have been wildly utilized for the treatment of cancer. [9][10] Recently, transition metal complexes have been developed as chemical reagents capable of altering Aβ aggregation. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Among many of these transition metal complexes, cyclometalated Ir(III) complexes would be one of the most promising candidates as their photophysical and photochemical properties are unique and desirable.…”
Section: Introductionmentioning
confidence: 99%